Women and the Wall: Gender Attitudes and Political Engagement in Unified Germany - de Vries, Catherine; O’Brien, Diana (The University of Chicago Press, 2026)
Women are generally less likely to express an interest in politics, join political organizations, and participate in political activities. Scholars posit that gender-(in)egalitarian attitudes are an important determinant of women’s political engagement. Yet, existing work finds mixed support for this claim. Using the German General Social Survey (1991–2016), we compare citizens’ attitudes toward gender across birth cohorts from East and West Germany. We find that cohorts socialized in the East hold more progressive gender attitudes than West Germans. We then show that traditional gender attitudes are negatively correlated with political interest and participation and that this effect is somewhat greater for women. Importantly, women who hold gender-egalitarian attitudes are nearly as politically engaged as men. We then assess the robustness of these results, show the findings hold in cross-national analyses, and explore an individual-level mechanism underlying our results. Together, our findings reveal an important barrier to political engagement.
Keywords: 59 Ciencia Política; ODS 10 - Reducción de las desigualdades